PERLINDUNGAN KORBAN KEJAHATAN DALAM HUKUM POSITIF INDONESIA - HB Sujiantoro (Faculty of Law, Universitas Pattimura, 2016)
Protection of victims of crime is necessary for the realization of a sense of justice. The victims in positive law of Indonesia have not gained a fair place and sometimes even forgotten. So it has an impact on the absence or lack of legal protection for victims of crime. In the judicial process, the victims are often forgotten, so the judge's decision has not been able to fulfill the sense of justice for the perpetrator, the victim, or the public. In some cases of crime, the victim may also contribute to the onset of a crime.